Pelatihan Perbanyakan Tanaman Hias Dengan Metode Tunggul dan Tak Dinodai Bagi Kelompok Perempuan PKK - Catalina Aurora Rose (Lembaga Pengembangan Kinerja Dosen, 2024)
As more and more people are doing activities at home due to the COVID-19 pandemic, members of the Mandal PKK group are encouraged to care for various types of local and imported ornamental plants. There are many types of